Carbon dioxide induced panic attacks and short term clonazepam treatment: preliminary study - ANTONIO EGIDIO NARDI; ALEXANDRE M. VALENÇA; WALTER ZIN; ISABELLA NASCIMENTO (Arquivos de Neuro-Psiquiatria)
AIMS: 1. To verify the sensibility of panic patients to a mixture of 35% CO2 and 65% O2. 2. To determine if a ten days treatment with clonazepam attenuates the panic attacks induced by the inhalation of 35% carbon dioxide in panic disorder. METHOD: We randomly selected six panic disorder subjects, using the Structured Clinical Interview for DSM-IV. All subjects went double-blindly through an inhalation of 35% CO2 and compressed gas (atmospheric air) on two occasions. First, at baseline, when they were drug free. Second, after a 10 days clonazepam treatment. RESULTS: Neither at baseline nor after treatment any patient had a panic attack during compressed gas inhalation. At the first test five patients (83.3%) had a severe panic attack with high levels of subjective anxiety during carbon dioxide inhalation. After 9.6 (± 3.4) days of clonazepam treatment, only two (33.3%) patients experienced a mild panic attack. CONCLUSION: This pilot study suggests the efficacy of the short term clonazepam therapy in attenuating panic attacks and supports the usefulness of the 35% carbon dioxide challenge test as an analogue method for study the efficacy of anti-panic drugs. Further placebo-controlled studies to pharmacological treatment are warranted.